Lessons Learned from Coronavirus Disease 2019 by Tunisian Dentists - Besbes, Amira; Abbes, Amira; Chattu, Vijay Kumar; Sioud, Sameh (Cerrahpaşa Medical Journal, 2024)
Objective: This survey aimed to highlight the epidemiological and psychological consequences of coronavirus disease 2019 (COVID-19) on Tunisian dentists. Methods: This cross-sectional study was conducted in 2020 among Tunisian dentists. The epidemiological impact concerned the frequency of patients’ reception before and after the pandemic and measures taken to prevent infection transmission. The psychological impact was assessed using the Generalized Anxiety Disorder (GAD) 7 test. Results: Totally, 206 dentists participated to the survey. This study showed that 80.6% of the respondents had suspended or limited their practice to emergencies only during the lockdown of March 22, 2020. After the lockdown, the number of patients consulting each day considerably decreased. The personal protective equipment was reinforced by 93.2% of the dentists in spite of difficulties in providing them. The most felt emotions were concern (60.2%) and anxiety (50.5%). The mean GAD score was 6.86 ± 4.95. Dentists were anxious about the infection risk, their patients’ economic level, and their professional future. Conclusion: Coronavirus disease 2019 emergency has negatively impacted the Tunisian dentists. Cite this article as: Besbes A, Abbes A, Chattu VK, Sioud S. Lessons learned from coronavirus disease 2019 by Tunisian dentists. Cerrahpaşa Med J. 2024;48(1):93-97.